Studi Etnobotani pada Ritual Keagamaan Tujuh Bulanan Masyarakat Kerinci : Studi Etnobotani pada Ritual Keagamaan Tujuh Bulanan Masyarakat Kerinci - Lia Angela; Muhammad Alfian; Agusminarti Agusminarti (Symbiotic: Journal of Biological Education and Science, 2023)
This study aims to classify and understand the variations and types of ethnobotany found in the seven-monthly religious rituals of the Kerinci people. This study is a type of qualitative research that uses descriptive methods. The research informants consisted of indigenous figures, religious figures, and members of the Kerinci community. Samples were taken from these various circles using the purpositive method of sampling.